The Ukrainian West : culture and the fate of empire in Soviet Lviv - Risch, William Jay (Cambridge, Mass. : Harvard University Press, 2011)
In 1990, months before crowds in Moscow and other major cities dismantled their monuments to Lenin, residents of the western Ukrainian city of Lviv toppled theirs. William Jay Risch argues that Soviet politics of empire inadvertently shaped this anti-Soviet city, and that opposition from the periphery as much as from the imperial center was instrumental in unraveling the Soviet Union. Lviv's borderlands identity was defined by complicated relationships with its Polish neighbor, its imperial Soviet occupier, and the real and imagined West. The city's intellectuals--working through compromise rather than overt opposition--strained the limits of censorship in order to achieve greater public use of Ukrainian language and literary expression, and challenged state-sanctioned histories with their collective memory of the recent past. Lviv's post-Stalin-generation youth, to which Risch pays particular attention, forged alternative social spaces where their enthusiasm for high culture, politics, soccer, music, and film could be shared. The Ukrainian West enriches our understanding not only of the Soviet Union's postwar evolution but also of the role urban spaces, cosmopolitan identities, and border regions play in the development of nations and empires. And it calls into question many of our assumptions about the regional divisions that have characterized politics in Ukraine. Risch shines a bright light on the political, social, and cultural history that turned this once-peripheral city into a Soviet window on the West.
Lviv and postwar Soviet politics -- The making of a Soviet Ukrainian city -- The new Lvivians -- The Ukrainian "Soviet abroad" -- Language and literary politics -- Lviv and the Ukrainian past -- Youth and the nation -- Mass culture and counterculture.
Includes bibliographical references (pages 267-344) and index.
Print version record.
In English.
eBooks on EBSCOhost
Keywords: Lʹviv (Ukraine) -- History -- 20th century; Lʹviv (Ukraine) -- Politics and government -- 20th century; Lʹviv (Ukraine) -- Social conditions -- 20th century; Nationalism -- Ukraine -- Lʹviv -- History -- 20th century; Ethnicity -- Ukraine -- Lʹviv -- History -- 20th century; Ukrainian language -- Political aspects -- Ukraine -- Lʹviv -- History; Lʹviv (Ukraine) -- Relations -- Soviet Union; Lʹviv (Ukraine) -- Relations -- Europe; Soviet Union -- Relations -- Ukraine -- Lʹviv; Europe -- Relations -- Ukraine -- Lʹviv; Nationalisme -- Ukraine -- Lvov -- Histoire -- 20e siècle.; Ethnicité -- Ukraine -- Lvov -- Histoire -- 20e siècle.; Ukrainien (Langue) -- Aspect politique -- Ukraine -- Lvov -- Histoire; Europe -- Relations -- Ukraine -- Lvov; HISTORY -- Europe -- Eastern; HISTORY -- Europe -- Former Soviet Republics; HISTORY -- Europe -- Russia & the Former Soviet Union; POLITICAL SCIENCE -- Political Ideologies -- Nationalism & Patriotism; Ethnicity; International relations; Nationalism; Politics and government; Social conditions; Ukrainian language -- Political aspects; Europe; Soviet Union; Ukraine -- Lʹviv; Ukraine -- West; Lemberg; Lemberg; Politik -- historia; Nationalism -- historia; Etnicitet -- historia; Internationella relationer -- historia; Ukrainska språket -- politiska aspekter -- historia; Ukraina -- Lviv; 1900-1999; History